Program Pengabdian, Service Learning Ala Pondok Pesantren Al Urwatul Wutsqo Jombang dalam Pembentukan Sikap Moderat Santri - Hasan, Moch. Sya’roni; Azizah, Mar’atul; Sintasari, Beny; Solechan, Solechan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This study describes the implementation of a service learning program at Al Urwatul Wutsqo Islamic Boarding School as a form of community service for the students. Utilizing a qualitative case study approach and collecting data through interviews and documents, the research findings indicate that the program has followed ideal procedures. However, there is a need to improve the monitoring and evaluation system for better structure. Service learning has proven effective in shaping the religious moderation character of the students, focusing on providing moderation education, group interactions, community service in diverse settings, and reflective learning. The primary recommendation involves enhancing the capacity of field supervisors and partner institutions to maximize their facilitating role in developing students' moderation. Despite some weaknesses in the evaluation, the conclusion affirms that the program successfully imparts religious moderation values through direct experiences in the community.Program Pengabdian, Service Learning Ala Pondok Pesantren Al Urwatul Wutsqo Jombang dalam Pembentukan Sikap Moderat Santri